Impact Performance of Ultra-High Performance Fiber Reinforced Concrete Beam and its Analytical Evaluation. Issue 2 (June 2014) - Fujikake, Kazunori
The aim of this study was to experimentally examine the impact performance of an Ultra-High Performance Fiber Reinforced Concrete (UHPFRC) beam and to develop an analytical model to represent its impact response. Thus, a drop hammer impact test was performed to investigate the influence of drop height of the hammer on the impact response of the UHPFRC beam. The impact test revealed that UHPFRC beams had excellent impact resistance compared to conventional RC beams. To attain the development of the analytical model, a comprehensive approach was adopted as follows in this study. First, the effects of strain rate on the compressive and tensile mechanical properties of UHPFRC specimens were investigated through a rapid loading test to formulate a rate-dependent constitutive model for UHPFRC. Subsequently nonlinear analysis based on a fiber model technique was developed to predict the load-midspan deflection relationship of a UHPFRC beam under high rate loading and was verified with the data obtained from the rapid loading test of UHPFRC beams. Finally, the response of a UHPFRC beam subjected to a drop hammer impact could be well demonstrated by the two degrees of freedom mass-spring-damper system model formulated through this comprehensive study.